Implementation Of Android-Based Learning Media In System Courses Management Information - Sri Restu Ningsih; Liranti Rahmelina; Heru Saputra; Ongky Alexander (Jurnal Abdimas Cendekiawan Indonesia, 2024)
The Community Service Partner (PkM) is AMIK Depati Parbo Kerinci, where the problem that occurs is that the learning media used is still conventional, such as lecturers providing material and assignments orally and in writing. Apart from that, if the lecturer is unable to attend, the material and assignments are delegated to the teaching team, sometimes making students not understand the content of the material. This PkM activity aims to implement an Android-based e-task application in the Management Information Systems course, which is an online learning system used for Android-based student assignment applications. This system was created using the Android Studio programming language, and uses the Waterfall method with system development tools, namely Unified Modeling Language (UML). Apart from that, the current learning process still uses a one-way method, namely the source of knowledge only comes from lecturers, making students less independent in learning because nowadays there are quite a lot of learning media models, one of which is Android-based learning media. The result of this activity is increased student independence in the teaching and learning process because it uses learning media in the form of an Android-based e-task application so that there is innovation in learning to make students more enthusiastic, creative and active in learning both online and offline.